(untitled) (Journal of Nepal Geological Society, 2013)
The flood disaster of May 5th, 2012 in Pokhara Valley, Nepal, taking the life of at least 72 people, is explained by a so-called sturzstrom. It developed from a huge rockfall onto a glacier in a high- mountain depression and then transformed into a subsequent debris flow/hyper-concentrated flow devastating the upper reaches of Seti Khola Valley. Apparently, the same processes have formed the smooth terrace landform of Pokhara Valley during Holocene times: two gigantic debris-flow events were identified and dated to have occurred about 12,000 and 750 years ago. Both epochs were associated with global warming processes. During these debris-flow events the whole valley was filled by 3-5 km3 of debris transported from the same huge high- mountain depression called Sabche Cirque where the recent debris flow came from. A new catastrophe of similar size would have an apocalyptic impact: about half a million people live in the valley today. A detailed investigation of the circumstances of the disaster on May 5th, especially the possible influence of global warming on the trigger of the disaster, and a reliable forecast of a potential recurrence of similar events or of even much greater scope, are urgently required. For this, the thorough understanding of the conditions, triggers and mechanisms of the huge flows in the past to compare it with the recent flood is indispensable as well.